2022
DOI: 10.1371/journal.pone.0267734
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the COVID-19 vaccine hesitancy spectrum

Abstract: Vaccine hesitancy remains an issue in the United States. This study conducted an online survey [N = 3,013] using the Social Science Research Solution [SSRS] Opinion Panel web panelists, representative of U.S. adults age 18 and older who use the internet, with an oversample of rural-dwelling and minority populations between April 8 and April 22, 2021- as vaccine eligibility opened to the country. We examined the relationship between COVID-19 exposure and socio-demographics with vaccine intentions [eager-to-take… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 32 publications
2
22
0
Order By: Relevance
“…A number of prior observational research showed that the lack of confidence in COVID-19 vaccines [ 45 ], adverse effects [ 58 ], and misinformation [ 48 , 49 , 59 , 60 ] contributed to vaccine hesitancy, while perceived severity [ 46 ] of and susceptibility [ 61 ] to COVID-19, and a greater sense of collective responsibility [ 31 ] increased willingness to be vaccinated. It is worth noting that most of these findings were documented to predict vaccination intention among general adults in the early stage of vaccine rollout, except for only a few studies that examined unvaccinated individuals [ 33 , 58 ]. Focusing on unvaccinated young adults in their 20s 16 months after the initial vaccine rollout, this study advances the literature on COVID-19 vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prior observational research showed that the lack of confidence in COVID-19 vaccines [ 45 ], adverse effects [ 58 ], and misinformation [ 48 , 49 , 59 , 60 ] contributed to vaccine hesitancy, while perceived severity [ 46 ] of and susceptibility [ 61 ] to COVID-19, and a greater sense of collective responsibility [ 31 ] increased willingness to be vaccinated. It is worth noting that most of these findings were documented to predict vaccination intention among general adults in the early stage of vaccine rollout, except for only a few studies that examined unvaccinated individuals [ 33 , 58 ]. Focusing on unvaccinated young adults in their 20s 16 months after the initial vaccine rollout, this study advances the literature on COVID-19 vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on COVID-19 and vaccine hesitancy research does not broadly address long-COVID-19 [ 33 , 34 , 35 , 36 , 37 ]. However, studies on people who have experienced COVID-19 or who have been exposed to the experiences of people close to them revealed that there is a significant relationship between vaccine hesitancy and these experiences [ 67 , 68 , 69 ]. Moreover, vaccine hesitancy and fear may be different before and after vaccination based on the side effects.…”
Section: Discussionmentioning
confidence: 99%
“…One of the prime reasons for this increase can be linked to vaccine hesitancy due to COVID in many countries [ 64 , 65 , 66 ]. Notably, people’s vaccine hesitancy was found to be associated with a plethora of personal and vicarious COVID-related experiences [ 67 , 68 , 69 ]. The authors of this study explored the possibility that long-lasting symptoms (i.e., long-COVID) may affect vaccine hesitancy levels, as was observed in the case of other COVID-related experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Research regarding ‘vaccine hesitancy’ shows that globally roughly 60%–70% of the population assent to being vaccinated or have already received it,1 2 while 20%–25% are against it, and the rest is undecided,3–7 although estimates depend on the population being studied and the particular phase of the pandemic. The international cross-sectional iCARE study revealed that during the first year of the pandemic, vaccination hesitancy (defined as not being extremely likely to be vaccinated) increased significantly from 25.6% to 29.9% overall, with some countries such as France or Turkey even exceeding 50% 2.…”
Section: Introductionmentioning
confidence: 99%